Technology-Based Management Strategies for Bullying Prevention in Junior High Schools: A Systematic Literature Review - Alfiani Nur Julia; Supadi; Desi Rahmawati; Cynthia Mayang Sari (South Sulawesi Education Development (SSED), 2026)
This study aims to identify and analyze technology-based management strategies for bullying prevention in junior high schools through a Systematic Literature Review (SLR) approach that adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework . The research employs a qualitative descriptive method by reviewing 30 peer-reviewed journal articles published between 2020 and 2025. Data sources were obtained from both international and national academic databases, selected based on their relevance to educational management, information technology, and school-based bullying prevention. The analysis reveals that technology-based strategies play a pivotal role in constructing adaptive, responsive, and collaborative school management systems. The dominant approaches include the utilization of digital reporting systems, online training platforms for teachers, self-reporting applications for students, and behavior-monitoring systems driven by data analytics. Findings further indicate that technological interventions are most effective when accompanied by strong managerial policies and supported by an inclusive school culture. This study underscores the necessity of integrating technological innovation with sound school management policies to foster a safe, healthy, and bullying-free educational environment